Sejmiki lutowe 1792 r. w relacjach „Gazety Narodowej i Obcej” i „Gazety Warszawskiej” - Kwiatkowska-Jeznach, Eliza (Acta Universitatis Lodziensis. Folia Historica, 2014)
The aim of regional councils in February 1792 was to remove the adverse image surrounding the Constitution of May the 3rd which some feared could cause a political coup. The councils were feautured heavily in the newspapers, „Gazeta Warszawska” and „Gazeta Narodowa i Obca”. Both newspapers included stories on 70 regional councils from across the Polish-Lithuanian Commonwealth, which represented 89% of the 78 meetings that took place. There is a difference between current and past opinion on the 3rd of May refferendum. Newspapers reported only two examples of support in the form of oath and gratitude by the councils forthe Constitution of May the 3rd. Today we can distinguish amongst the oath, affirmation, thanks and silence. The differences between the past press interpretation and current research on the results of regional councils in February 1792 relates almost exclusively to the information published by „Gazeta Narodowa i Obca”. This newspaper misinterpreted 34% of the 70 presented regional councils. In comparison „Gazeta Warszawska” insccurately published only one news story from across the Polish-Lithuanian Commonwealth. It should be noted that they reported only on 6 regional councils and those whose results did not raise any doubts. The regional councils of Ferbraury 1972 were first recognised by the Polish newspaper referendum. Unfortunately, none of the newspapers provided a fair report. This was caused by the views of the editors of both newspapers – Julian Ursyn Niemcewicz and father Stefan Łuskina. The readers of „Gazeta Narodowa i Obca” inevitably received a manipulated version of the regional councils, and the readers of „Gazeta Warszawska” were therefore mislead of the marginal role in the February events.